Development of Green Chemistry Oriented Student Worksheets with Guided Inquiry Model to Improve Science Literacy Skills on Reaction Rate Material - Pratiwi, Karina Rike; Mitarlis, Mitarlis (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Green chemistry plays a crucial role in minimizing the environmental impact of chemical processes, while science literacy equips students with the knowledge and skills to understand a sustainable future. This study aims to describe the feasibility of a Student Worksheet oriented toward green chemistry using a guided inquiry model, deemed suitable for enhancing students’ scientific literacy skills in the reaction rate topic. The research method employed is the Research and Development (R&D) 4D model, which includes define, design, develop, and disseminate stages, limited in this study to the development stage to analyse needs, design, and test the conformity of the learning media. A limited trial was conducted with 30 eleventh-grade students who had previously received instruction on reaction rate and green chemistry at a senior high school in Nganjuk during the 2024/2025 academic year. Data were collected through questionnaires, observations, and tests, then analyzed quantitatively and descriptively using mode, percentage, Guttman scale, Likert scale, and N-Gain test. The results show that the worksheet is valid in terms of content and construct (mode 4, good category), practical based on student responses (97.5%, very good), student activities (96.86%, very good), and implementation (mode 5, very good). The worksheet was also effective in improving scientific literacy, as evidenced by 90% of students achieving a gain score ≥ 0.7 (high category). N-Gain by indicator: context 0.85, knowledge 0.85, and competence 0.88. Based on its validity, practicality, and effectiveness, the developed worksheet is feasible to use as a learning medium.